Can Universities Help “Build Back Better” in Education? The Socially Embedded University Responds to the Covid-19 Pandemic - Reimers, Fernando M. (Frontiers in Sustainability, 2021)
The high impact disruptions in the external environment caused by the Covid-19 pandemic revealed the socially embedded character of many universities around the world. University collaborations with schools during the pandemic suggest that they are institutions open to their external environment, capable of learning from and with their environment, and capable of influencing their external environment, helping to address significant social challenges. Drawing on a non-probabilistic survey administered to a convenience sample of 101 universities in 21 countries, I examine how they built partnerships with schools to sustain educational opportunity during the pandemic. The results are informative of the evolving nature of higher education and its mission. They illustrate the responsiveness of universities to societal needs. The findings show that universities are socially connected to their surrounding context, and that they see themselves as engines of social innovation at a time of great unexpected need. The study found the majority of universities to be engaged with schools supporting education during the pandemic. They see such engagement as part of their mission and strategy, even though they perceive it as challenging. Most of such engagements do not have a formalized “theory of action,” but are evolving as the crisis created by the pandemic itself evolved. While such engagement during the pandemic builds on pre-existing engagements with schools, the response during the pandemic provided an opportunity to integrate different efforts across various units. The majority of the universities in the study had a school of education, and about half have a program of pre-service teacher education and few of the collaborations established during the pandemic were new, most were based on pre-existing collaborations. In two thirds of the cases the collaborations with schools during the pandemic were initiated by University leaders. Most of the collaborations consist of developing alternative delivery channels and supporting teachers in developing new skills to teach remotely.